Penggunaan Media Sosial dan Market Place Untuk Mengembangkan Pemasaran UMKM - Ustadus Sholihin; Imam Mukhlis (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The use of social media and market places for MSMEs Hantaran to the city of Kediri is very necessary and important. The main objective of this research is the use of social media and market places to develop marketing from offline to online and increase sales of Hantaran MSME products in the city of Kediri. With a qualitative descriptive type of research. The research subjects of the Hantaran UMKM group in Kediri city numbered 28 members. The research results for social media with the highest results are Instagram, then Tik Tok, Facebook, WA Business and finally YouTube. Meanwhile, the highest marketplace is Shopee, then Tokopedia and finally Lazada. The hope is that if you want to progress and increase the development of marketing products online, Hantaran actors must be ready to adapt to changing times and continue to learn how to operate social media and market places.